Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae) - Novelo-Gutiérrez, Rodolfo (Zootaxa, 2018)
Cordulegaster virginiae sp. nov. is described based on eight adults (7 males, 1 female) collected in cloud forest in municipalities of Banderilla and Xalapa, Veracruz, Mexico. The new species is compared with adults of C. diadema Selys, 1868. All the structural differences between both species are located on the abdomen. Cordulegaster godmani McLachlan, 1876 is considered a junior synonym of C. diadema. The larva of C. diadema is redescribed and illustrated in detail based on reared material.